Modelling of collisions of the automobiles - Sokolovskij, Edgar; Mikaliūnas, Šarūnas (Transport, 2006)
The graphic analytical modelling and the computer modelling of collisions of the automobiles are compared in this article. The examples of modelling of collisions of the automobiles are given. The computer modelling of collision of the automobiles with the help of the program PC CRASH is introduced. The possibilities and advantages of this computer program, the inserted parameters and their optimization are investigated. The possibilities of applying the computer modelling program in the experts’ examination of traffic accidents while modelling collisions of the automobiles, the items and requirements raised towards the experts, who work with such programs, on reliability of the obtained results are considered.First Published Online: 27 Oct 2010